Rare instances of individuals with autism supporting or engaging in terrorism. Issue 2 (12th June 2017) - Faccini, Lino; Allely, Clare S.
Abstract : Purpose: The prevalence of individuals with an autism spectrum disorder (ASD) being associated with terroristic threats, lone wolf terrorism or affiliating with terroristic groups is rare. This paper aims to discuss this issue. Design/methodology/approach: However, several cases are presented, where individuals with autism are involved in making a naïve, empty terroristic threat or uttering serious serial terroristic threats. Other cases are also presented of individuals being at risk for an abduction or being used by a terrorist group, and finally committing an act of domestic lone wolf terrorism. Findings: Essential to the analysis was establishing a functional connection between autism-based deficits and the terroristic threats, terrorism, and when to not criminalize naïve, empty terroristic threats or acts. Originality/value: Currently, tools available to law enforcement and prosecutors exploit the vulnerabilities and liabilities which arise as a result of group interactions, a "preventive" approach to terrorism that is not applicable to the solitary, "lone wolf" terrorist. There has been relatively little research (including case studies) examining individuals with ASD who engage in terrorism. For instance, when dealing with an individual with ASD who is charged with terrorism, it is crucial to consider how the diagnosis of autism may have presented as a contextual vulnerability, and to make sure that justice, rehabilitation and management, are informed by an understanding of the person's diagnosis of ASD.